Self-reported health and depression among EIRA cohort: a moderated mediation model of sex and perceived social support - Sánchez-Recio, Raquel; Oliván-Blázquez, Bárbara; Méndez-López, Fátima; Gascón-Santos, Santiago; Martí-Lluch, Ruth; Zabaleta-Del-Olmo, Edurne; Tamayo-Morales, Olaya; Maderuelo-Fernández, José A.; Casajuana, Marc; López-Jiménez, Tomas; Motrico, Emma; Gómez-Gómez, Irene; et al. (Frontiers in Psychology, 2025)
BackgroundThe positive relationship between health and good perceived social support has been widely demonstrated in the scientific literature. It is known that having a good social support influences the proper maintenance of health even as a protective factor, besides being a good predictor in the recovery of health during a disease process, influencing differently men and women.AimThis project aims to study the moderating effects of perceived social support in the relationship between depression and self-perceived health according to gender, after a complex multiple-risk intervention was carried out in patients of primary health care with low social support.MethodsA cluster randomized clinical trial was developed in the subgroup of patients included in phase 3 of the EIRA project. CONSORT recommendations were followed to present the results. To determine the mediating effect between social support and self-perceived health, three regression analyses were carried out using the procedure designed by Hayes through the PROCESS macro for SPSS.Results3,062 people (54.9% women) participated in the study. Men reported experiencing more social support and self-perceived health (p < 0.001) than women at the beginning of the study, but women reported higher social support at post-intervention. Moderation analyses showed that, post-intervention, those women (bsimple = −2.9867, p < 0.001) and males (bsimple = −1.4337, p < 0.001) who scored lower in depression reported higher social support.ConclusionIn primary care, it is necessary to encourage intervention strategies that promote social networks as a key element of positive action aimed at maintaining and improving the population’s health, especially in adults and more specifically in women.Clinical trial registrationClinicalTrials.gov, identifier NCT03136211.